2006
DOI: 10.1097/01.wnp.0000231273.22681.0e
|View full text |Cite
|
Sign up to set email alerts
|

Neurophysiological Changes in Neurologically Asymptomatic Hypothyroid Patients: A Prospective Cohort Study

Abstract: This is a prospective cohort study on neurologically asymptomatic patients with primary hypothyroidism. It was conducted to evaluate the frequency and pattern of neurophysiological changes in this group of patients. Twenty-three subjects were included over a period of 2(1/2) years. Neurophysiological evaluation included nerve conduction studies (NCS) of median, ulnar, and peroneal motor nerves as well as median palmar and ulnar and sural sensory responses. Electromyography of deltoid, first dorsal interosseous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
33
1
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 22 publications
4
33
1
3
Order By: Relevance
“…These findings are consistent with that reported by Kececi et al 2006 [14] and El-Salem K et al 2006 [15]. However, the sample size for Kececi et al is more than our study.…”
Section: Discussionsupporting
confidence: 71%
“…These findings are consistent with that reported by Kececi et al 2006 [14] and El-Salem K et al 2006 [15]. However, the sample size for Kececi et al is more than our study.…”
Section: Discussionsupporting
confidence: 71%
“…Altered Schwann cell metabolism may cause mucinous deposition, which results in nerve entrapment and demyelination [9,15,29]. Severe metabolic defects in neurons may also disturb axonal transport and lead to axonal atrophy [9,15,29]. Vascular nerve damage secondary to hypothyroid-induced alternations in the blood-nerve barrier may also cause demyelination [9,15,29].…”
Section: Discussionmentioning
confidence: 99%
“…Altered Schwann cell metabolism may cause mucinous deposition, which results in nerve entrapment and demyelination [9,15,29]. Severe metabolic defects in neurons may also disturb axonal transport and lead to axonal atrophy [9,15,29].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies that have examined nerve conduction parameters in hypothyroid patients reported that deficiency of thyroid hormones causes motor neuropathy by affecting different peripheral nerves, but, more commonly, the median nerve (4,5,6). A number of retrospective studies reported the prevalence of neuropathy to be between 10 and 70% in patients with hypothyroidism (1,7,8,9). The most common form of peripheral entrapment neuropathy is carpal tunnel syndrome (CTS) (10).…”
Section: Introductionmentioning
confidence: 99%